Efektivitas Program Bantuan Pangan Non Tunai Dalam Pengentasan Kemiskinan Di Kabupaten Ponorogo - Putri Rahayu; Hanik Fitriani (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
Poverty is the inability of individuals to meet their needs economically. One of the programs for poverty alleviation is Non-Cash Food Assistance (BPNT). The problems in the field are still many recipients of Non-Cash Food Assistance that need to be corrected. The primary purpose of this study is to analyze the realization of the BNPT program in poverty alleviation in Ponorogo district, to analyze the obstacles encountered by the BPNT program in the Ponorogo Regency area in poverty alleviation, and to analyze the effectiveness of the BPNT program in poverty alleviation in Ponorogo district. This research uses qualitative methods. The findings of this study are 1) Realization of the Non-Cash Food Assistance Program (BPNT) in Ponorogo district, namely to reduce the expenditure burden through meeting food needs. BPNT distribution involves Warung Agents taking food ingredients such as vegetables, eggs, etc. 2) Constraints of the BPNT program in poverty alleviation in Ponorogo district: inappropriate personal data resulted in the Prosperous Family Card not being issued. 3) The effectiveness of the BPNT program in poverty alleviation in Ponorogo district includes: Target accuracy needs to be more effective, Program socialization has not been effective, Program objectives have been effective, Program monitoring has not been effective because monitoring from the assistance is still ineffective.